(untitled) (Teacher’s World: Journal of Education and Research, 2023)
Due to COVID-19 pandamic, students all over the country had to get detached from the normal flow of education. The non-government schools of the urban areas started online education using mainly Zoom and WhatsApp media platforms. This study explores the challenges experienced by both teachers and students during the COVID-19 pandemic while involved in the mathematics teaching-learning process. The study followed an exploratory case study research design. Qualitative data were collected through semi-structured interviews via zoom/ mobile phone meetings with 10 primary school teachers and 20 students of primary level and analysed thematically. Also, 10 online primary mathematics classes were observed for data triangulation. This study explored three perspectives curriculum-related challenges, teacher’s challenges and students’ challenges. It is found that appropriateness of the content, alignment of contents concerning time schedules, curriculum objectives and teaching strategies proposed in the curriculum are the major curriculum-related challenges faced by teachers while conducting mathematics classes online. Besides, delivering the lecture, managing the class, assessing students, teachers’ lack of technological knowledge and availability of physical facilities were also identified as challenges in terms of teachers’ perspective. Another finding of this study is that students faced different challenges (e.g. technological, motivational, collaborative work, homework, feedback, and home environment) while learning through an online platform. Based on the study’s findings, the practical implications for academic institutions, curriculum developers, teachers’ trainers and policymakers have been articulated. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.185-203